Estudo da influência de nanopartículas de ouro na atividade de lipase de Pseudomonas fluorescens imobilizada em nanopartículas superparamagnéticas - Reis, Eduardo Arizono dos (2020)
The growing interest in the application of biocatalysts in several industrial sectors made the enzymatic immobilization stand out among the possible strategies to enable the use of these catalysts. This strategy has the main advantage of stabilizing the biocatalyst even in changes in temperature, pressure and pH, however, there are disadvantages such as the loss of activity in relation to the free biocatalyst and the empiricism of the technique. To overcome these problems, different supports, immobilization protocols and biocatalytic systems have been studied. One of the focuses of this work was to remove the empiricism of the immobilization technique using factorial planning. For this, magnetic nanoparticles were chosen as a support due to the ease of separation from the reaction medium with the use of an external magnetic field. Thus, to evaluate the influence of the surface modification of magnetic particles in the enzymatic immobilization process, magnetite nanoparticles were synthesized by the solvothermal method using stabilizers with different liquid charges: cationic, zwitterionic and anionic. From the XRD results, it is observed that the magnetic supports synthesized in the presence of anionic surfactant were smaller (≈10 nm), however, the particles synthesized in the presence of the cationic surfactant showed higher densities of amine groups than the other two particles. Pseudomonas fluorecens lipase was chosen as a model enzyme to develop factor planning in the optimization of variables in the immobilization protocol. The optimized parameters were lipase concentration, nanoparticle mass, cross-linker concentration, pH and immobilization time. It was observed that only pH had the greatest effect on immobilization, in which the lower the pH the greater the efficiency of immobilization, reaching a maximum at pH 5, close to the isoelectric point of the enzyme (pI = 4.7). It was observed that the greater the immobilization efficiency, the higher the conversion values of soybean oil into fatty acid esters by hydrolysis followed by esterification. Among the optimized nanoparticles, it was observed by TEM that in the coating process there was an agglomeration of the same and a consequent decrease in the surface area, however, a better conversion was observed for the agglomerated nanoparticle than for the more dispersed nanoparticles. The reuse of the support after the denaturation of the immobilized enzymes was also tested and it was observed that it is possible to reuse the support in up to 3 consecutive immobilization cycles while maintaining the enzyme activity. When studying the influence of gold nanoparticles (AuNPs), it was observed that the order of addition of the gold particles on the enzymes interferes in the result, in which the addition of AuNPs after the immobilization of lipase in the magnetic nanoparticles caused a worsening of catalytic response. On the other hand, adding AuNPs to lipase before immobilization resulted in an improvement of up to 50% in the hydrolytic activity of the enzyme immobilized in the presence of light when compared to the activity of enzyme without AuNP. When compared to the activity of the immobilized enzyme in the absence of light, there was an improvement in the activity of about 4 times in the activity of the enzyme after the incidence of light in the system.